Potensi Tepung Cangkang Telur dalam Pengembangan Berbagai Inovasi Makanan Berbasis Kalsium Alami - Muhammad Bahrul Ilmi (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2025)
The addition of calcium from eggshell powder is known to have a relatively high absorption rate of 45.59%.The method used in this article is a literature article using review article technique. The articles used in this article were obtained through a search using several search google scholar. The keywords used in the search were tailored to the problem, namely